Satellite-Based Risk Analysis Mapping For Urban Development In Kuantan District, Pahang - Amir Asyraf, Mohd Fauzi (2022)
Urban growth and development cities are among the major drivers of natural hazard growth, especially flood disasters. Developing cities not only experienced high risk of flood occurrences, but triggers plenty human-wildlife conflicts. Kuantan has a lot of land space but limited spaces of sustainable green corridor. Lack of green spaces indicates the low capacity of the natural ecosystem to combat the anomalies of the natural phenomenon such as excessive precipitation which led to local scale of natural hazards like flood and stagnant water. The objectives of this research which are to generate high- to-low risk indicator to minimize potential of human-wildlife conflict according to existing GI distribution using remote sensing approach and to develop flood risk map analysis of Kuantan, Pahang using satellite-based approach and GIS tools. Next, to spatially distribute GI according to high-to-low risk indicator to minimize potential of human-wildlife conflict. This study is to focus on area in Kuantan, Pahang as the pilot site with a variation of topological features, undulating surface, and current natural hazards. Begin at phase 1 it consists of data collection and data processing to achieve the first objectives in Chapter 1. Phase 2 consists of data presentation. Then, after the verifications process, the map generation to produce final outcomes. The flood risk map is influenced by precipitation parameters as a result of the high weight assigned during the AHP method. Besides, it has been categorized in 5 levels of risk classes which are very low, low, moderate, high, and very high zones of flood. The results show that the very high flood areas covered were Tanjung Lumpur, Berserah and Balok. Meanwhile, this map is regressed with NDVI value that produced from red and near infrared band of Landsat. The highest hotspot was recorded at east side of Kuantan district, which is Teluk Cempedak area whereby, the lower NDVI value, the higher human wildlife conflict occurred. By developing this map, it has been generated where a total of 25% of Kuantan area was indicated as the most vulnerable zone for flood hazard, 40% moderate risk and 35% identified as low risk zone. This flood risk map provides a crucial improvement of flood control strategies and preparing an evacuation plan for authorities. Indirectly, the combination of NDVI and HWC is important because the highest vegetation index, the lowest human wildlife conflict occur. Thus, the location with the highest vegetation index was selected as green corridor.